Analisis Semiotika Logo Milad ke-112 dan Tanwir Muhammadiyah: Representasi Budaya dan Filosofi Sosial dalam Identitas Visual - Fadillah, Dani (ANALOGI Jurnal Ilmu Sosial dan Humaniora, 2025)
The logo for the 112th Anniversary and Tanwir of Muhammadiyah embodies a rich meaning, representing the local cultural philosophy of the Sasando and Sepe Flower as symbols of harmony, sustainability, and collaboration. This study aims to analyze the semiotic meaning embedded in the logo using Charles Sanders Peirce's theory of signs. This approach allows researchers to explore the visual elements within the logo and how these elements reflect Muhammadiyah’s vision of bringing prosperity for all, in alignment with this year's overarching Tanwir theme. The study employs a qualitative descriptive method, analyzing visual signs and the local cultural context that contribute to the formation of meaning. The findings reveal that the logo not only reflects the organization’s identity but also emphasizes key messages of social collaboration, sustainability, and respect for diversity, all of which contribute to Muhammadiyah’s vision of creating inclusive and sustainable prosperity.